Correction: Biswas, M.S. et al. Inactivation of Carbonyl-Detoxifying Enzymes by H2O2 Is a Trigger to Increase Carbonyl Load for Initiating Programmed Cell Death in Plants. Antioxidants 2020, 9, 141 - Md. Sanaullah Biswas; Ryota Terada; Jun'ichi Mano (MDPI AG, 2020)
The author wishes to make the following correction to this paper [...]